2018
DOI: 10.1155/2018/5629304
|View full text |Cite|
|
Sign up to set email alerts
|

The Chinese Medicine, Jiedu Recipe, Inhibits the Epithelial Mesenchymal Transition of Hepatocellular Carcinoma via the Regulation of Smad2/3 Dependent and Independent Pathways

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors worldwide. In China, traditional Chinese herb medicine has been widely used in the treatment of HCC. Jiedu Recipe (JR) is a common used prescription which has shown good results against HCC. However, the exact mechanisms of JR are still unknown. Therefore, we investigated the efficacy of JR on HCC in the current study. JR inhibited the cell viability of both SMMC-7721 and Huh7 cells in both time- and dose-dependent manners. Transwell ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…[ 7,8 ] Recent developments in molecular and cell biology have led to significant insights into the biological functions of CHM and have shown that some medicines can inhibit tumor cell invasion, metastasis, angiogenesis, and the epithelial–mesenchymal transition and induce cell death. [ 9,10 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,8 ] Recent developments in molecular and cell biology have led to significant insights into the biological functions of CHM and have shown that some medicines can inhibit tumor cell invasion, metastasis, angiogenesis, and the epithelial–mesenchymal transition and induce cell death. [ 9,10 ]…”
Section: Introductionmentioning
confidence: 99%
“…3 At present, surgical resection is the best treatment strategy for HCC. 4 However, the outcomes of patients with HCC remain unsatisfactory due to late diagnosis, distant metastasis, and high recurrence rate. 5 Traditional Chinese medicine (TCM), a hot spot for tumor treatment, has several advantages, and has been widely used for the treatment of diverse cancer types in China.…”
Section: Introductionmentioning
confidence: 99%
“…And the findings suggest that RvD1 inhibits cell proliferation and the expression of inflammatory cytokines in LPS-treated liver cancer cells by targeting the MAPK pathway in HepG2 cells 25 . TGFβ1 treatment increased the phosphorylation of Smad2/3, p38 MAPK, JNK, ERK1/2, and Akt in SMMC-7721 cells and pretreatment with JR blocked TGFβ1-induced activation of Smad2/3 and Akt and MAPKs in HCC 37 . But in other research, Puerarin inhibited proliferation of SMMC-7721 cells and promoted their apoptosis in a dose- and time-dependent fashion (p < 0.05).…”
Section: Discussionmentioning
confidence: 90%